Numerical study on flow characteristics in the primary side of a once-through steam generator under ocean conditions - Chen, Xiting; Lu, Xianghui; Gao, Yaxin; Mao, Yulong; Hu, Yisong; Zhu, Jianmin; Chen, Jun (Frontiers in Energy Research, 2024)
The flow characteristics of the primary side of the helical coil once-through steam generator (OTSG) have a significant impact on the safe operation of the reactor. Different from the land-based stationary working conditions, the flow of the primary side of the OTSG is influenced by sea waves and winds under ocean conditions. The rigid body motion model is used to calculate the flow of the primary side under different ocean conditions, including heeling, trimming, rolling, pitching, heaving, and combined conditions. The results show that under heeling and trimming conditions, the static pressure of the primary side is different from that under vertical conditions due to the influence of gravity, but its impact on the flow field is relatively small. Under rolling and pitching conditions, the mean flow velocity and pressure drop change periodically with the movement of the OTSG, and the smaller the sway angle, the smaller the variation amplitude of the mean flow velocity and pressure drop. Under the heaving condition, the variation amplitude of the mean flow velocity is greater than that under rolling and pitching conditions, and reverse flow occurs. Under the combined heaving and rolling condition, the mean flow velocity and pressure drop are influenced by the period and amplitude of both the two motions.